Peningkatan Kapasitas Komunikasi Kader dalam Upaya Menurunkan Angka Stunting di Kecamatan Bayongbong - Kurniawan, Achmad Wildan; Latifah, Hanny; Fanaqi, Chotijah; Margani, Aan (Penerbit Goodwood, 2024)
Purpose: This community service activity aims to reduce the stunting rate in Bayongbong District by increasing cadres' communication skills in providing information about health to the community because cadres play an important role in socializing health programs to the community. Methodology: The activity methods used include: 1) the preparation stage, namely approaching the target audience, which begins with carrying out observations first, obtaining permission from the relevant agencies, and providing initial motivation to cadres who take part in service activities; and 2) the program implementation stage, which includes lectures, case studies, discussions, and the final evaluation stage. Results: The results of this service showed positive results by achieving knowledge and understanding of cadres related to the application of effective communication in conveying good information to the public. Cadres as participants in this activity expressed their readiness to convey health information to the public through effective communication strategies. Limitations: Health workers and related agencies need to play a role in socializing health programs to increase the credibility of the information conveyed to the public. Therefore, collaborative efforts are needed among government institutions, community leaders, and cadres. Contributions: This community service increases the communication capacity of cadres to inform the community about health programs.